ANALISIS PENGARUH PENDAPATAN, JUMLAH NASABAH, DAN PANDEMI COVID-19 TERHADAP PENYALURAN KREDIT KCA PADA PT. PEGADAIAN (PERSERO) UPC SECANG - Fandi Adi Setyawan (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2020)
Overall, this article will discuss how the influence of income, number of customers, and the Covid-19 pandemic on KCA lending to PT. Pegadaian (PERSERO) UPC Secang. The data in this article, obtained from the daily pawn loan customers data, calculated from January to April. In the research conducted, the authors used qualitative research methods, so the data obtained were calculated rigidly. The results obtained in this study, after going through the calculation and data processing are income does not affect lending, customers do not influence lending, and the condition of the Covid-19 pandemic does not affect lending.